Financial frictions and monetary policy reaction in Sierra Leone: a bayesian DSGE approach - Emerson Abraham Jackson; Mohamed Samba Barrie (West African Financial and Economic Review, 2023)
This paper uses a Bayesian estimation approach to examine the behavior of the Sierra Leone's economy by creating a small-open economy DSGE model that includes financial frictions. The study utilises a New Keynesian framework to examine the actions of diverse economic agents, such as households, enterprises, the monetary authority, and the financial sector. The primary aim is to assess the model's realism in representing the monetary policy transmission in Sierra Leone. The results indicate that monetary policy shocks are temporary and that the Bank of Sierra Leone ought to increase policy rates in reaction to elevated inflation. Nonetheless, there are deficiencies in the transmission of monetary policy, rendering it ineffectual in regulating inflation or stimulating productivity. Depreciation of the exchange rate results in a significant transmission of imported inflation. The paper indicates that financial frictions do not affect output, inflation, or the monetary policy rate. The findings offer valuable insights for policymakers and underscore the advantages and constraints of monetary policy in regulating inflation and stimulating output in Sierra Leone.
Keywords: E12; E32; E52; G01; 330; Financial Frictions; Bayesian DSGE Model; Open Economy; Sierra Leone